Implementation of Post-Quantum Cryptography Algorithms for Financial Applications in Indonesia - Sutriawan; Enggar Novianto (Ran Edu Center, 2025)
The development of quantum computing poses a serious threat to classical cryptographic algorithms that have been used to protect digital data and financial transactions. Algorithms such as RSA and Elliptic Curve Cryptography (ECC) are vulnerable to quantum computer attacks capable of running Shor's algorithm to efficiently solve large number factorization problems. This study aims to explore and analyze the implementation of Post-Quantum Cryptography (PQC) algorithms, specifically Falcon and Dilithium, in the context of digital financial systems in Indonesia. The research approach was conducted through literature studies and case study analysis on the Algorand platform, which has adopted the Falcon algorithm to strengthen digital signature security. The results of the study show that the integration of PQC algorithms can be done without sacrificing system efficiency, while providing a significant increase in security resilience against quantum threats. This research is expected to serve as a reference for financial institutions and national regulators in formulating transition strategies towards a secure digital security infrastructure in the quantum era.